Microbial analysis and antimicrobial resistance screening of drinking water in the Qassim Region of Saudi Arabia using mass spectrometry technology: Analyzing drinking water for microbes - Elbehiry, Ayman; Aldubaib, Musaad; Abalkhail, Adil (Cellular and Molecular Biology, 2025)
Water intended for human consumption must be devoid of harmful bacteria that can lead to waterborne illnesses. Consequently, there is a pressing need for a rapid and precise method to identify bacterial contaminants in drinking water. The objective of this study was to investigate the protein profiles of various bacterial species present in water through the application of protein fingerprinting (PF) and real-time polymerase chain reaction (real-time PCR) techniques, as well as to evaluate their antimicrobial resistance. A total of two hundred water samples were collected from five distinct locations within the Qassim region of Saudi Arabia. Bacterial isolates were identified using a protein fingerprinting analytical technique (PFAT), which was subsequently confirmed by real-time PCR. The Kirby-Bauer method was employed to assess antibiotic resistance among the bacterial isolates. Out of the 200 water samples analyzed, PFAT successfully identified 123 bacterial isolates, with the most frequently isolated species being 48 Pseudomonas aeruginosa (P. aeruginosa), 17 Staphylococcus aureus (S. aureus), and 16 Escherichia coli (E. coli). All waterborne bacterial isolates were accurately identified 100% of the time, achieving a score of 2.00 or higher. The results from real-time PCR indicated that 87.5% of P. aeruginosa isolates were positive for the oprI gene, all S. aureus isolates were positive for the nuc gene, and 93.75% of E. coli isolates were positive for the fliC gene. P. aeruginosa isolates demonstrated a high level of resistance to aztreonam (64.6%), while S. aureus exhibited significant resistance to cefoxitin and cefepime (88.24%), followed by aztreonam (82.35%) and amoxicillin-clavulanate (70.6%). E. coli isolates showed complete resistance to ampicillin (100%), with high resistance also observed against amoxicillin-clavulanate and cefoxitin (87.5%), and cefepime (81.25%). This study underscores the significance of utilizing PFAT for the microbiological identification of diverse water samples as a reliable and effective method. Furthermore, it emphasizes the necessity for regular surveillance and monitoring of antimicrobial-resistant bacteria in drinking water sources.